Self-regulation, taxation and public voluntary environmental agreements - Thomas P. Lyon; John W. Maxwell (Fondazione Eni Enrico Mattei (FEEM), 2000)
An increasingly popular instrument for solving environmental problems is the "public voluntary agreement (VA)", in which government offers modest technical assistance and positive publicity to firms that reach certain environmental goals. Prior papers treat such agreements as a superior, low-cost instrument that can be used to pre-empt a threat of traditional, inefficient, regulation. We present a more general model in which public Vas may instead be weak tools used when political opposition makes environmental taxes infeasible. We explore the conditions under which taxes, public VAs, and unilateral industry actions are to be expected, the implications for industry size, as well as the welfare implications of the various instruments.
Keywords: D72; K32; L51; Q28; 330; Self-regulation; public voluntary agreements; environmental regulation; Selbstverpflichtung; Ökosteuer; Vergleich; Wohlfahrtsanalyse; Theorie